2015
DOI: 10.1371/journal.pone.0121328
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2-Deficiency Suppresses Cell Proliferation through Disturbance of Autophagy

Abstract: Mitofusin2 (Mfn2), a mitochondrial outer membrane protein serving primarily as a mitochondrial fusion protein, has multiple functions in regulating cell biological processes. Defects of Mfn2 were found in diabetes, obesity, and neurodegenerative diseases. In the present study, we found that knockdown of Mfn2 by shRNA led to impaired autophagic degradation, inhibited mitochondrial oxygen consumption rate and cell glycolysis, reduced ATP production, and suppressed cell proliferation. Inhibition of autophagic deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…Most recently Ding et al (2015) have shown that knockdown of the Mfn2 gene with shRNA inhibited not only oxygen consumption, but also glycolysis and cell proliferation and reduced cellular ATP content. These data probably confirm the differences between cellular response to acute and persistent deficiency of mitofusin 2 [ 31 ]. Our data shown here indicate that stable depletion of Mfn2 gene induces adaptive processes counteracting disorganization of cell metabolism and function and preventing severe abnormalities.…”
Section: Discussionsupporting
confidence: 66%
“…Most recently Ding et al (2015) have shown that knockdown of the Mfn2 gene with shRNA inhibited not only oxygen consumption, but also glycolysis and cell proliferation and reduced cellular ATP content. These data probably confirm the differences between cellular response to acute and persistent deficiency of mitofusin 2 [ 31 ]. Our data shown here indicate that stable depletion of Mfn2 gene induces adaptive processes counteracting disorganization of cell metabolism and function and preventing severe abnormalities.…”
Section: Discussionsupporting
confidence: 66%
“…Mitofusin2 (Mfn2) is a guanosine triphosphatase (GTPase) dynamin-like protein of the outer mitochondrial membrane, and mutations in genes that encode Mfn2 can be associated with neurological disorders [13]. It is also involved in various pathologic conditions, ranging from neurodegeneration to diabetes and obesity, and different crucial cellular processes, including cell proliferation, survival or death, and maintenance of mitochondrial deoxyribonucleic acid stability [14]. As an important regulator of tissue fibrosis and cell proliferation, Mfn2 is a direct target gene of miRNA-214, which negatively regulates Mfn2 expression by translational inhibition [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent report indicated that defect of mitochondrial fusion protein Mfn2 impaired autophagy-induced degradation, subsequently decreasing mitochondrial oxygen consumption rate and cell glycolysis, reducing ATP production, and suppressing cell proliferation. 73 Therefore, FSH-induced autophagy is a regulatory mechanism that ensure the order and timing of cell cycle transition by mitophagy activation through the PINK1-Parkin pathway ( Figure 8h ), which may help reducing follicle atresia and GC apoptosis. 74 …”
Section: Discussionmentioning
confidence: 99%